2013
DOI: 10.1016/j.juro.2012.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Versus Laparoscopic Management of Noninvasive Upper Tract Urothelial Carcinoma: 20-Year Single Center Experience

Abstract: For G1 upper tract urothelial carcinoma, endoscopic management can provide effective oncologic control and renal preservation. However, endoscopic management should not be considered for higher grade disease except in compelling imperative cases or in patients with poor life expectancy as oncologic outcomes are inferior to those of laparoscopic nephroureterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 28 publications
0
40
0
4
Order By: Relevance
“…Tumor grade was another impact factor of oncologic outcome. Cutress et al (Cutress et al, 2013) found that compared with nephroureterectomy, kidney preservation treatment had significantly lower survival rate of IRFS, PFS, CSS and OS in G2 and G3 but equivalent in G1. On the other hand, grade 2 and grade 3 upper tract urothelial carcinoma was significantly poor compared with grade 1 (Grasso et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor grade was another impact factor of oncologic outcome. Cutress et al (Cutress et al, 2013) found that compared with nephroureterectomy, kidney preservation treatment had significantly lower survival rate of IRFS, PFS, CSS and OS in G2 and G3 but equivalent in G1. On the other hand, grade 2 and grade 3 upper tract urothelial carcinoma was significantly poor compared with grade 1 (Grasso et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we selected the one with more areas and patients. After rounds of screening, twenty-three studies including 1587 KS and 3996 NU patients were enrolled meta-analysis at last (Hall et al, 1998;Shiraishi et al, 2003;Chen et al, 2005;Roupret et al, 2006;Giannarini et al, 2007;Lehmann et al, 2007;Lucas et al, 2008;Dragicevic et al, 2009;Gadzinski et al, 2010;Jeldres et al, 2010;Raymundo et al, 2011;Bin et al, 2012;Bing-bing et al, 2012;Colin et al, 2012;Grasso et al, 2012;Bagrodia et al, 2013;Cutress et al, 2013;Fajkovic et al, 2013;Klatte et al, 2013;Dalpiaz et al, 2014;Fukushima et al, 2014;Hoffman et al, 2014;Hung et al, 2014). All included studies were retrospective comparative study; no randomized controlled trials were identified.…”
Section: Literature Filtration and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, retrospective analysis suggests that patients with low-grade and low-stage disease benefit from a nephron-sparing surgery with similar outcomes at five years to those achieved with RNU. 6 The aim of this study is to assess the long-term oncological results in terms of recurrence, specific survival, and global survival, as well as the preservation of the renal unit in the conservative treatment of UUTC. …”
mentioning
confidence: 99%
“…5,7 Inaccurate diagnosis from ureteroscopic biopsy can negatively affect patient prognosis and prevent optimal clinical management. 9 Several optical imaging technologies have been proposed to improve the diagnosis of UTUC, with the goal to better stratify patients for renal-sparing management options and long-term endoscopic surveillance. Feasibility studies have been reported using narrow band imaging, 10 photodynamic diagnosis, 11 and optical coherence tomography.…”
mentioning
confidence: 99%